Therapeutic and anti-inflammatory effects of baricitinib on mortality, ICU transfer, clinical improvement, and CRS-related laboratory parameters of hospitalized patients with moderate to severe COVID-19 pneumonia: a systematic review and meta-analysis. Issue 10 (3rd October 2022) - Tahsini Tekantapeh, Sepideh; Ghojazadeh, Morteza; Ghamari, Ali Akbar; Mohammadi, Aida; Soleimanpour, Hassan
ABSTRACT: Background: Due to the high incidence and mortality of the worldwide COVID-19 pandemic, beneficial effects of effective antiviral and anti-inflammatory drugs used in other diseases, especially rheumatic diseases, were observed in the treatment of COVID-19. Methods: Clinical and laboratory parameters of eight included cohort studies and five Randomized Control Trials between the baricitinib group and the control group were analyzed on the first day of admission and days 7, 14, and 28 during hospitalization. Results: According to the meta-analysis result of eight included cohort studies with 2088 patients, the Pooled Risk Ratios were 0.46 (P < 0.001) for mortality, 6.14 (P < 0.001) for hospital discharge, and the mean differences of 76.78 (P < 0.001) for PaO2 /FiO2 ratio was −47.32 (P = 0.02) for CRP, in the baricitinib group vs. control group on the seventh or fourteenth day of the treatment compared to the first day. Based on the meta-analysis of five RCT studies with 11, 825 patients, the pooled RR was 0.84 (P = 0.001) for mortality and 1.07 (P = 0.014) for patients' recovery. The mean differences were −0.80 (P < 0.001) for hospitalization days, −0.51(P = 0.33) for time to recovery in the baricitinib group vs. control group. Conclusions: Baricitinib prescription is strongly recommended in moderate to severe COVID-19.